Design of thin curved sensor to measure contact slip in fretting experiments - Rajendran, Raja Pandi; Kaliveeran, Vadivuchezhian (Journal of Naval Architecture and Marine Engineering, 2022)
This paper proposes a new thin curved sensor/strip to measure the relative slip between pad and specimen under fretting condition. Since the relative contact displacement is an important parameter to categorize the fretting process, the measurement of contact displacement between pad and specimen is necessary. Because of high yield strength and the ability to return to its initial position even with notable deflection, the spring steel have chosen to fabricate the thin curved strip. Before the fabrication, the detailed Finite Element Analysis (FEA) of the thin curved sensor was carried out. The strip consists of different shapes (rectangular, circular and elliptical) of slots and the number of slots in each strip is varied from 2 to 6. The Strain Energy Approach (SEA) has been used to calculate the displacement for the curved strip and it was compared, verified and validated with its FEA and Experimental results. From FEA study of thin curved strip with slots, four configurations were chosen to measure micro level displacement between pad and specimen under fretting experiments. The study reveals that the increasing number and size of holes presented in the curved strip indicate that the increased in displacement and von-Mises stress values which offers the higher flexibility to the strip. The reduction in area and minimum thickness of the curved strip could be the reason for the decrease in the stiffness of the curved strip. This study explores the use of new simple and novel instrument/sensor to capture the micro level relative displacement between the pad and specimen under fretting condition.